Educação ambiental e coleta seletiva: um estudo de caso - Raffaeli, Maria das Graças da Costa (2002)
The present study evaluates the Program of Solid Waste Pick Up and its initiatives of Environmental Education in the district of São Francisco, in the City of Niterói, State of Rio de Janeiro. This pioneer experiment in Brazil, which lasted for almost seventeen years, has shown, throughout its results, that it is a reference for other projects of educational actions regarding the subject of solid waste. Furthermore, we can conclude that, this experiment also enables us to notice the efficiency of not formal and informal educational actions.